2020
DOI: 10.1002/mabi.201900276
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Sensitive Amphiphilic Non‐Ionic Triblock Copolymers for Enhanced In Vivo Skeletal Muscle Transfection

Abstract: It is reported that low concentration of amphiphilic triblock copolymers of pMeOx‐b‐pTHF‐b‐pMeOx structure (TBCPs) improves gene expression in skeletal muscle upon intramuscular co‐injection with plasmid DNA. Physicochemical studies carried out to understand the involved mechanism show that a phase transition of TBCPs under their unimer state is induced when the temperature is elevated from 25 to 37 °C, the body temperature. Several lines of evidences suggest that TBCP insertion in a lipid bilayer causes enoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…It was also conceivable that some therapeutic effects might be obtained if the appropriate therapeutic gene was used here instead of GHRH. In 2020, Rasolonjatovo et al prepared pMeOx-b-pTHF-b-pMeOx structure (TBCPs, Table 1) triblock copolymers to improve the efficiency of gene delivery to skeletal muscles [20]. Among them, TBCP1 (Figure 7; n = 7, m = 6) with the best effect of 1 mg/mL delivered pDNA encoding Luc to the TA muscles of mice.…”
Section: B Other Triblock Co-polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also conceivable that some therapeutic effects might be obtained if the appropriate therapeutic gene was used here instead of GHRH. In 2020, Rasolonjatovo et al prepared pMeOx-b-pTHF-b-pMeOx structure (TBCPs, Table 1) triblock copolymers to improve the efficiency of gene delivery to skeletal muscles [20]. Among them, TBCP1 (Figure 7; n = 7, m = 6) with the best effect of 1 mg/mL delivered pDNA encoding Luc to the TA muscles of mice.…”
Section: B Other Triblock Co-polymersmentioning
confidence: 99%
“…Among them, TBCP1 (Figure 7; n = 7, m = 6) with the best effect of 1 mg/mL delivered pDNA encoding Luc to the TA muscles of mice. The expression of Luc in TBCP1 was eight In 2020, Rasolonjatovo et al prepared pMeOx-b-pTHF-b-pMeOx structure (TBCPs, Table 1) triblock copolymers to improve the efficiency of gene delivery to skeletal muscles [20]. Among them, TBCP1 (Figure 7; n = 7, m = 6) with the best effect of 1 mg/mL delivered pDNA encoding Luc to the TA muscles of mice.…”
Section: B Other Triblock Co-polymersmentioning
confidence: 99%
“…[18] Modulation of the chemical nature of both blocks and the polymer architecture revealed that pluronic materials performances might be outperformed. [19][20][21][22] In parallel, the recent issue raised by poly(ethylene oxide) (PEG) immunogenicity favored the development of alternative hydrophilic polymers such as that polyoxazolines (POx) derivatives for biological applications. [23,24] In the field of nucleic acids delivery into skeletal muscles, polyoxazoline-based copolymers have already demonstrated their efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] In the field of nucleic acids delivery into skeletal muscles, polyoxazoline-based copolymers have already demonstrated their efficiency. [25] Rasolonjatovo et al [19] synthesized different amphiphilic triblock copolymers of poly(2-methyl-2-oxazoline)-bpolytetrahydrofuran-b-poly(2-methyl-2-oxazoline) with a phase transition lower critical solution temperature (LCST) in aqueous solutions depending on their molar masses and chemical compositions. They witnessed the importance of the copolymer phase transition around the physiological temperature to permit the interaction with cell membranes and an enhanced DNA translocation into cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were many literature reports on the MD simulation of phospholipid membranes [34][35][36][37][38], few reports were found on the MD simulation regarding the interaction of gene delivery materials, especially amphiphilic triblocks, with cell membranes, and many conjectures were still derived from experience and assumptions [2,22,23,29,[39][40][41][42]. Therefore, we will use MD simulation, taking the four pre-viously reported materials L64, LPL, rL 2 PL 2 , and rL 3 PL 3 as samples, to explore the mechanisms of their interactions with cell membranes by dynamically analyzing the intermolecular interactions and energy changes.…”
Section: Introductionmentioning
confidence: 99%